Emergent General Surgery Operations in Patients With Left Ventricular Assist Devices. Issue 1 (January 2021) - Bauman, Zachary M.; Cunningham, Robert; Hodson, Alex; Shostrom, Valerie; Evans, Charity H.; Schlitzkus, Lisa L.
Background: The left ventricle assist device (LVAD) patient population is rapidly expanding. Unique characteristics of these patients complicate the management of noncardiac surgical problems. Emergent general surgery (EGS) intervention is often warranted but remains poorly described. We reviewed EGS consultations in LVAD patients to better understand these patients. Methods: During a 12-year period, 301 LVAD patients were reviewed. Demographics, comorbidities, reason for EGS consultation, operative intervention, transplantation, and mortality were analyzed. Wilcoxon, Fisher's exact, and chi-square tests were used for analysis. Statistical significance was P < .05. Results: A total of 139 (46.2%) patients required EGS consultation. EGS consultations were older (63 vs 57 years; P = .002), primarily Caucasian (86%), and male (83%) with average preimplant cardiac index of 1.84. Comorbidities were similar between those with and without EGS consultation. Gastrointestinal (GI) bleeding was the most common reason for consultation (53%), followed by abdominal pain (22%) and bowel ischemia/obstruction (19%). Of EGS consultations, 77% were on warfarin and 60% on aspirin. Procedures were not withheld: 46% required esophagogastroduodenoscopy (EGD) and 30% required colonoscopy. Surgical intervention was performed in 28% of EGS consults—49% emergent (within 24 hours) and 44% urgent (during hospitalization). Mean time to surgery was 48 days after LVAD placement. EGS intervention precluded 7 (18%) patients from heart transplantation and 10 (26%) patients suffered perioperative mortality. Elevated lactic acid was associated with increased mortality. Conclusion: EGS consultation is necessary in almost half of all LVAD patients, most commonly for GI bleed. EGD/colonoscopy can be safely used to manage the majority of these consultations; one-third will require surgery. High lactic acid is associated with higher mortality. Additional analysis of this population is required for improving surgical management.